Using a Sight Word Measure to Predict Reading Fluency Problems in Grades 1 to 3. Issue 4 (4th July 2018) - Morris, Darrell; Perney, Jan
ABSTRACT: After considering the relationships between (a) reading fluency and reading rate and (b) reading rate and sight vocabulary, this study addressed a very practical question. Can a cut score on a sight vocabulary task (1-min) predict level of reading fluency 4+ months into the future? The prediction was tested at multiple times point across grades 1 - 3 ( N = 305). Results showed that a sight vocabulary cut score (Time 1) was very effective at identifying children who could read with a minimum level of fluency 4 months later (Time 2). The tasks used in the study (word recognition and oral reading) transfer directly to classroom use. They can be used to identify at-risk readers and to diagnose the nature of a fluency problem.